The renin secretion profile under the influence of sleep deprivation and the neuropeptides CRH and GHRH. (October 2020) - Künzel, H.; Schüssler, P.; Yassouridis, A.; Uhr, M.; Kluge, M.; Steiger, A.
Highlights: Sleep related renin secretion increases during the recovery night after sleep deprivation in healthy volunteers. The oscillations of renin related to the NREM-REM-cycle persisted after sleep deprivation, whereas renin concentration and the amplitude of renin secretion increased. Mean renin concentration is significantly negative correlated to the number of transitions from wake to sleep. After sleep deprivation renin concentration is positively correlated to SWS, δ power, σ power and SEI. Renin secretion was not found to be controlled by CRH or GHRH, but seems to be influenced by sleep deprivation. Abstract: It is already known that during normal sleep plasma renin activity (PRA) shows oscillations with decreases during rapid-eye-movement (REM) sleep and increases during non-REM (NREM) sleep. We also know that renin correlates positively with slow-wave sleep (SWS). Sleep deprivation is known to enhance significantly SWS and slow wave activity (SWA, known as δ power). Based on these findings we addressed the question whether and to which extent sleep deprivation may affect the synchronization found between PRA and REM sleep during normal sleep and whether this synchronization is affected by other sleep regulating factors. To investigate these questions we compared sleep EEG and sleep-related free renin levels in 48 normal women and men 19–69 years old between nights before and after 40 h of sleep deprivation. During the recovery night, four bolus injections of either GHRH, CRH or placebo were injected via long catheter around sleep onset. When compared to baseline after each of the treatments SWS, SWA and renin levels increased. The characteristical oscillation profiles of renin during normal sleep were also preserved after sleep deprivation. Similar to normal sleep our data support also a distinct link between nocturnal renin secretion and SWS after sleep deprivation and that independent of the applied treatments.